Green and sustainability criteria in Malaysia’s poultry production and management - Rahmat, Suharni; Abdul Hamid, Mohd Syaiful Rizal; Chew, Boon Cheong (Universiti Malaysia Terengganu, 2021)
This article discusses green and sustainability (G&S) criteria in poultry production in Malaysia. The study focuses on broiler production management from the downstream (farm management) to the upstream (end-user) processes. This study is important as it investigates new developments of the poultry industry in Malaysia. As this is an exploratory study, the study is conducted based on a case study of oa halal broiler company in Malaysia. Data was gathered through semi-structured interviews and observations of nine government agencies in Malaysia that are involved in poultry production. Thematic analysis and patterns were applied in analysing the data. The results show the G&S criteria described in the regulations and production process perspective. The four G&S criteria listed in the category of poultry content are: i) effective use of technology; ii) enhancing nutrition; iii) sustainable sourcing; and, iv) improving land and water management.